The Impact of Social Media on Social Interaction and Self-Identity in Indonesian Society - Aditya Panca Nugraha; Andini Kurnia; Puji Irawan Pratama Putra; Alip Rahman; Diky Dikrurahman (International Journal Labs, 2024)
The development of information and communication technology has changed the way humans interact. Social media, as one of these technological products, has become an inseparable part of everyday life. In Indonesia, social media use has increased significantly, especially among the younger generation. This research aims to identify the positive and negative impacts of social media on social interaction in Indonesian society. This study used qualitative research methods. The data collection technique in this research is a literature study. The data that has been collected is then analyzed in three stages: data reduction, data presentation, and drawing conclusions. The research results show that social media brings significant changes in social interactions and self-identity, including enriching social experiences, developing self-identity, simplifying the communication process, helping to build new communities, assisting individuals in expressing themselves, and increasing social awareness. However, this positive impact is also balanced by negative impacts, such as excessive use of social media leading to dependence and addiction, cyber bullying, privacy theft, social comparison, fake news, and the use of fake identities. The findings of this study have significant implications for policymakers, educators, and social media platform developers. Understanding the dual impact of social media on society can inform the creation of policies and educational programs that promote responsible social media use while mitigating its negative effects.